ChemInform Abstract: Unravelling the Properties of Supported Copper Oxide: Can the Particle Size Induce Acidic Behavior?. Issue 14 (20th March 2013) - Zaccheria, Federica; Scotti, Nicola; Marelli, Marcello; Psaro, Rinaldo; Ravasio, Nicoletta
Abstract Review: 96 refs.